2015
DOI: 10.1186/s13012-015-0307-0
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of clinical guidelines on diabetes and hypertension in urban Mongolia: a qualitative study of primary care providers’ perspectives and experiences

Abstract: BackgroundHypertension and diabetes, key risk factors for cardiovascular disease, are significant health problems globally. As cardiovascular disease is one of the leading causes of mortality in Mongolia since 2000, clinical guidelines on arterial hypertension and diabetes were developed and implemented in 2011. This paper explores the barriers and enablers influencing the implementation of these guidelines in the primary care setting.MethodsA phenomenological qualitative study with semi-structured interviews … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 33 publications
2
39
0
1
Order By: Relevance
“…15 Similarly a study done in China noted that increased workload made it difficult for health care professionals to adhere to the guidelines. 16 successful diabetic guidelines implementation. 16,17 Factor 2 category (Lack of information related factors) included items related to lack of diabetic guideline information in doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…15 Similarly a study done in China noted that increased workload made it difficult for health care professionals to adhere to the guidelines. 16 successful diabetic guidelines implementation. 16,17 Factor 2 category (Lack of information related factors) included items related to lack of diabetic guideline information in doctors and patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 successful diabetic guidelines implementation. 16,17 Factor 2 category (Lack of information related factors) included items related to lack of diabetic guideline information in doctors and patients. Other studies have also identified lack of knowledge and culturally sensitive diabetic education as a barrier to diabetes guideline implementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result revealed the majority of the key informants reported that the main barriers that prevented them from adhering to guideline recommendations of diabetes and hypertension were the time constraints and increased workload. 34 Higher provider workloads have potentially negative impact on patients’ quality of care, 35 patient satisfaction 36 and job satisfaction. 37 Time constraints largely increase with higher workloads.…”
Section: Discussionmentioning
confidence: 99%
“…Los esfuerzos por lograr su implementación surgen desde su planificación y elaboración, priorizando las recomendaciones a implementar, identificando barreras y facilitadores de manera que el proceso logre ajustarse al contexto y al personal de salud objetivo [12] . Un estudio previo realizado en Mongolia mostró que el tener capacitaciones que permitan un mejor conocimiento y entendimiento de una guía, genera en el receptor una mayor preparación y habilidades para poder brindar una adecuada atención primaria [13] . La falta de capacitación limita no sólo el entendimiento de la guía sino también su aplicación en la práctica diaria, obteniéndose mejores resultados y preparación cuando existe un entrenamiento teórico-práctico [12,14] .…”
Section: Discussionunclassified